Digitalisasi Pengambilan Keputusan Produksi melalui Aplikasi Mobile Berbasis TOPSIS pada UMKM - Soetam Rizky Wicaksono; Rudy Setiawan; Muhammad Nurwegiono (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2026)
Micro, Small, and Medium Enterprises (MSMEs) continue to face challenges in making operational decisions, particularly in determining production priorities, which are often based on intuition rather than systematic data analysis. This condition was identified at Dapur Mom Two R, a culinary MSME in Malang City, where production decisions considered sales volume, product profit, remaining stock, and customer ratings without an integrated evaluation mechanism. This community service program aimed to develop and implement an Android-based Decision Support System (DSS) using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to support objective production prioritization. The implementation method consisted of problem identification, system requirements analysis, application design, mobile application development, and integration of the TOPSIS algorithm into the application. The developed system provides features for product data management, criteria input, automatic TOPSIS calculation, and production priority ranking. The implementation results demonstrate that the application successfully integrates the TOPSIS algorithm into a mobile platform and is capable of automatically ranking products based on predefined criteria. The application has reached the implementation stage and is ready to be deployed in operational activities at the partner MSME. This digital solution is expected to facilitate data-driven decision making and strengthen digital transformation initiatives for MSMEs through practical adoption of mobile decision support technology.